MATURATION AND SPAWNING OF THE ANCHOVY THRYSSA MYSTAX IN THE NORTHERN ARABIAN SEA - Hoda, S M Shamsul (Indian Journal of Fisheries, 2011)
Maturity studies carried out on Thryssa mystax (Bloch & Schneider),collected from commercial landings at Karachi Fish Harbour, from January toDecember, 1977, show that the female-male ratio is 1.26 : 1, and, as revealed byova-diameter polygons, S'pawnmg occurs twice a year. There are two peak spawningseasons, in January-March and June-July, as borne out by the close approximationof GSI and relative condition coefficient. The minimum size at sexual maturitywas about 140 mm TL for both sexes. The relations between total length of fishand length and breadth of gonads, and between fish weight and gonad weight havebeen determined. The logarithmic relationships between fecundity and total lengthand body weight and ovary weight have also been eatablished